PENGARUH PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KERJA KARYAWAN TEKNIK LAPANGAN (Lembaga Pengembangan Kinerja Dosen, 2022)
Occupational safety and health (OHS) issues in Indonesia are generally still not optimal. This is indicated by the high number of work accidents. Low or poor employee health programs result in a tendency for low productivity levels. The purpose of this study was to analyze the effect of occupational safety and health on the work productivity of field engineering employees of Perumda Air Minum Tirta Bumi Sentosa Kebumen Regency. Data were collected from 35 field engineering employees of Perumda Air Minum Tirta Bumi Sentosa using a questionnaire. The data analysis methods used are validity test, reliability test, simple linear regression, t test and coefficient of determination with the help of IBM SPSS 24 software. The results of simple linear regression analysis show that Y = 8.288 + 0.263 X which means that occupational safety and health has a positive effect on work productivity. The t test results show that occupational safety and health (K3) has a significant effect on work productivity with a tcount value of 4.824 greater than the t table with a significance value of 0.000. The coefficient of determination is 0.396, which means that the occupational safety and health variable contributes 39.6% to the work productivity variable. While the remaining 0.604 or 60.4% is influenced by other factors not examined in this study.